A Meta-analysis on the Effects of Quantitative-Easing on Japanese Economic Growth - Ferreira-Lopes, A.; Linhares, P.; Martins, L.F.; Sequeira, T. N. (Society for Computation in Economics 25th International Conference on Computing in Economics and Finance (CEF 2019), 2019)
We present an original meta-probit analysis that focuses on the literature that has been studying the effectiveness of the Bank of Japan’s unconventional monetary policies during the 2001 to 2016 period. We measure effectiveness by overall significant and positive effects of the Impulse Response Functions in VAR-type models. The analysis based on funnel asymmetry and precision effect tests provides evidence of neither publication bias nor a consensus over the output growth effects during the quantitative easing years. A thorough meta-probit analysis suggests that certain variables included in the primary studies models (industrial output, price level, bond yield, and either the money base or the money supply – as well as different specifications in the data used – increasing the number of observations used or choosing quarterly data) affect the probability of reporting statistically significant (positive) effects of quantitative easing on output growth.